Japanese encephalitis virus infection in non-encephalitic acute febrile illness patients - Ma’roef, Chairin Nisa; Dhenni, Rama; Megawati, Dewi; Fadhilah, Araniy; Lucanus, Anton; Artika, I Made; Masyeni, Sri; Lestarini, Asri; Sari, Kartika; Suryana, Ketut; Yudhaputri, Frilasita A.; Jaya, Ungke Anton; et al. (PLoS neglected tropical diseases, 2020)
Although Japanese encephalitis virus (JEV) is considered endemic in Indonesia, there are only limited reports of JEV infection from a small number of geographic areas within the country with the majority of these being neuroinvasive disease cases. Here, we report cases of JEV infection in non-encephalitic acute febrile illness patients from Bali, Indonesia. Paired admission (S1) and discharge (S2) serum specimens from 144 acute febrile illness patients (without evidence of acute dengue virus infection) were retrospectively tested for anti-JEV IgM antibody and confirmed by plaque reduction neutralization test (PRNT) for JEV infection. Twenty-six (18.1%) patients were anti-JEV IgM-positive or equivocal in their S2 specimens, of which 5 (3.5%) and 8 (5.6%) patients met the criteria for confirmed and probable JEV infection, respectively, based on PRNT results. Notably, these non-encephalitic JE cases were less likely to have thrombocytopenia, leukopenia, and lower hematocrit compared with confirmed dengue cases of the same cohort. These findings highlight the need to consider JEV in the diagnostic algorithm for acute febrile illnesses in endemic areas and suggest that JEV as a cause of non-encephalitic disease has likely been underestimated in Indonesia.